로바젯정으로 유발된 간수치 상승 환자의 한방 치료 증례 보고 - 강희경; 조임학; 이찬; 허기윤; 김민화; 권정남; 김소연; 박성하; 윤영주; 이인; 최준용; 홍진우; et al. (대한한방내과학회지, 2021)
Objective: This study evaluated a clinical case of a patient with Rovazet-induced abnormal liver function treated with intradermal acupuncture. Method: A 59-year-old woman with abnormal liver function induced by Rovazet ceased taking the drug and instead received intradermal acupuncture treatment. After 15 days, clinical symptoms and laboratory test results were evaluated. Results: Aspartate aminotransferase and alanine aminotransferase levels decreased, and clinical symptoms such as nausea and fatigue improved after treatment with intradermal acupuncture and cessation of the Rovazet. Conclusion: This study meaningfully examined a clinical case of a patient with abnormal liver function induced by a lipid-lowering agent, which is uncommon in Korea. Unfortunately, the lack of clear evidence and the use of only one case are limitations of the study.